2012
DOI: 10.1517/14740338.2012.720970
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of immunomodulators and biologics during pregnancy and lactation for the treatment of inflammatory bowel disease

Abstract: Introduction The inflammatory bowel diseases (IBD) are chronic, idiopathic, inflammatory conditions of the gastrointestinal tract that peak in incidence during the reproductive years. Therefore, the safety of IBD medications during pregnancy and lactation is of significant interest to many patients. Unfortunately, the current pregnancy labeling used by the United States Food and Drug Association (FDA) is often misinterpreted and may mislead healthcare providers and their patients to believe that risk increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Because the peak incidence of the disease occurs between 20 and 40 years of age, this is of great concern for women in their reproductive years, especially the effect of IBD medications on the developing fetus. 119 It is thought that as long as IBD is under control prior to conception, the disease will remain in a state of quiescence throughout pregnancy. 120 Disease activity at conception has been associated with preterm births, LBW, and fetal loss.…”
Section: Inflammatory Bowel Disease and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Because the peak incidence of the disease occurs between 20 and 40 years of age, this is of great concern for women in their reproductive years, especially the effect of IBD medications on the developing fetus. 119 It is thought that as long as IBD is under control prior to conception, the disease will remain in a state of quiescence throughout pregnancy. 120 Disease activity at conception has been associated with preterm births, LBW, and fetal loss.…”
Section: Inflammatory Bowel Disease and Pregnancymentioning
confidence: 99%
“…Prospective studies have shown that GDM treatment can reduce PreE by 30% and a recent case report has shown that dietary management in addition to insulin therapy can resolve angiogenic imbalance and improve pregnancy outcomes. 119 To optimally select patients for clinical trials, it would be useful to have rapid, reliable tests for detecting intra-amniotic inflammation and/or microbial invasion of the amniotic cavity. Combs et al suggest several different tests, including 16 rDNA polymerase chain reaction (PCR), rapid bedside tests for IL-6, MMP-8, and other inflammatory mediators, and proteomic profiling of amniotic fluid or cervicovaginal secretions.…”
Section: Prevention or Treatment-is It Possible?mentioning
confidence: 99%
“…Reassuringly, apart from a weak increase in incidence of preterm births and low birth weight babies, neither CD nor UC are associated with other adverse pregnancy or health outcomes 6-15 . Furthermore, most of the current medications for treatment of IBD may be safely continued during pregnancy and in the post-partum period 10, 16-18 .…”
Section: Introductionmentioning
confidence: 99%